2014
DOI: 10.1136/sextrans-2014-051745
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of a lifetime history of sexually transmitted infections among women who have sex with women in Toronto, Canada: results from a cross-sectional internet-based survey

Abstract: This research is among the first to examine intrapersonal, interpersonal and structural factors correlated with an STI history among WSW. Findings highlight the importance of STI prevention strategies for WSW to be tailored to sexual identity, with particular attention to bisexual women's needs. Interventions should connect to sexual healthcare, address sexual stigma and train HCP to better meet the needs of WSW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 28 publications
2
41
0
7
Order By: Relevance
“…1-10 Studies in Canada 7,11 and the US 12 report that one-fifth of LBQ women have a lifetime history of STI-similar to STI infection rates among heterosexual women. 2,6,13,14 The limited research examining LBQ women's sexual practices has revealed inconsistent uptake of safer sex strategies.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…1-10 Studies in Canada 7,11 and the US 12 report that one-fifth of LBQ women have a lifetime history of STI-similar to STI infection rates among heterosexual women. 2,6,13,14 The limited research examining LBQ women's sexual practices has revealed inconsistent uptake of safer sex strategies.…”
Section: Introductionmentioning
confidence: 88%
“…29 A cross-sectional study of WSW in Toronto, Canada, indicated that women identifying as bisexual had higher selfreported lifetime STI history rates than lesbian or queer identified women. 11 Social and structural drivers operate as distal influences on individual and group level HIV and STI vulnerability by constraining or enabling individual practices and access to sexual health services. 30,31 For example, sexual stigma is associated with reduced uptake of safer sex practices among men who have sex with men 32 and higher rates of STI among LBQ women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, approximately twice as many heterosexual women and three times as many bisexual women reported being diagnosed with any of the assessed STIs compared to lesbian women. This finding reinforces some previous work indicating that bisexual women are indeed at an increased risk for some STIs relative to both lesbian and heterosexual peers, on a nationally representative level (Johnson et al, 1987;Lindley, et al, 2008;Logie, et al, 2015;Everett, 2013). These results are also consistent with several prior studies indicating that lesbian women are at lower (but not negligible) risk for STI transmission (Young & Meyer, 2005;Bauer & Welles, 2000).…”
Section: Risk For Infertility As Function Of Sexual Identity Sexual supporting
confidence: 89%
“…A survey of 2,345 lesbian and bisexual women who participated in the 2006 National College Health Assessment found that bisexual-identified women were the most likely to report having had an STD in the past year (at 9%), lesbian women were the least likely to report the same (at 2%), and heterosexual women were in between (at 6%) (Lindley et al, 2008). Similarly, in a Canadian sample of women who have sex with women, bisexual-identified women were more likely than lesbian women to have ever been diagnosed with an STI (Logie, 2015). Finally, in a study investigating the intersection of sexual identity and sexual behavior among participants of the National Longitudinal Survey of Adolescent Health, women who identified as bisexual and heterosexual were nearly three times as likely as lesbian women to report having ever been diagnosed with and STI, regardless of their previous partners' genders (Everett, 2013).…”
Section: Risk For Infertility As Function Of Sexual Identity Sexual mentioning
confidence: 99%